Comparative analysis of sweet cherry cultivars on their ecological and biological indicators - Surányi, D. (International Journal of Horticultural Science, 2022)
Sweet cherries are slightly more demanding than sour cherries. It is grown in warmer areas around the world. The relative ecological values obtained for the varieties obtained by extensive data collection differ slightly from the leading descriptions. Warm and demanding. The woody parts tolerate the cool of the winter quite well, the flower buds are damaged by the spring frosts. Its water demand is medium, in the case of 550 mm of annual rainfall, it adorns well on loose soils with good nutrient supply. Airy ground, neutral soil (pH 5.5-7.5) is optimal, but not suitable for areas with strongly calcareous, stagnant, stagnant groundwater. From the start of ripening, sudden rainfall, stormy winds and birds can cause great damage. Highlighting the world’s leading varieties in the study (Bing, Rainier, Chelan, Van and Burlat) (Iezzoni et al., 1991, Faust & Surányi, 1997) - according to relative ecological and biological values, the most popular cherries are mainly they differed from the other varieties based on TB and KB. Open pollination and with it, the productivity of the varieties exceeded the overall variety average precisely because of the breeding objectives. Certainly, the analysis of historical varieties, the oldest landscape and local varieties based on relative ecological and biological values can help further pomological-ecological research.